2022
DOI: 10.1128/msystems.00649-22
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Lysine Acetylation in Antibiotic Resistance of Escherichia coli

Abstract: The misuse of antibiotics has resulted in the emergence of many antibiotic-resistant strains which seriously threaten human health. Protein post-translational modifications, especially acetylation, tightly control bacterial metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The pykF was up-regulated by 1.35 log2 (FC), while the pykA was down-regulated by 1.06 log2 (FC). The studies have reported that pykF is a key upstream kinase to catalyze phosphoenolpyruvate (PEP) producing ATP and promoting energy metabolism causing the sensitivity of drug-resistant strains (Zuye et al 2022 ). Abdelhamid et al ( 2019 ) have demonstrated that pykA plays the dominant role in glycolysis, which is relevant for Pseudomonas aeruginosa virulence, and it is able to influence bacterial pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The pykF was up-regulated by 1.35 log2 (FC), while the pykA was down-regulated by 1.06 log2 (FC). The studies have reported that pykF is a key upstream kinase to catalyze phosphoenolpyruvate (PEP) producing ATP and promoting energy metabolism causing the sensitivity of drug-resistant strains (Zuye et al 2022 ). Abdelhamid et al ( 2019 ) have demonstrated that pykA plays the dominant role in glycolysis, which is relevant for Pseudomonas aeruginosa virulence, and it is able to influence bacterial pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Protein acetylation in bacteria may serve many functions, including regulation of central metabolism, growth control, virulence, and biofilm formation [ 1 , 46 , 54 , 55 , 56 , 57 ]. On the global level, acetylation may increase stress resistance [ 42 , 58 ], prevent excessive carbon flux, or serve as a storage mechanism for carbon subunits in the cell [ 9 ]. Acetylation may also protect proteins against irreversible detrimental modifications such as carbonylation or glycation, since all these modifications may occur on the lysine residue [ 9 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that protein aggregation and acetylation may be responsible for antibiotic resistance or tolerance in E. coli and other Gram-negative bacteria [ 11 , 29 , 30 , 40 , 41 , 42 ]. One example is the correlation between the aggregation of endogenous E. coli proteins and persisters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug resistance of A. fumigatus can be caused by various mechanisms, including intrinsic aberrant gene expression and external environment effectors ( 23 ). Drug resistance is significantly influenced by acetylation and deacetylation ( 24 ), phosphorylation and dephosphorylation ( 25 ), succinylation and desuccinylation ( 26 ), and glycosylation and deglycosylation ( 27 ). Lysine succinylation is a newly identified protein PTM that is vital in cellular physiology.…”
Section: Introductionmentioning
confidence: 99%